2017
DOI: 10.1186/s12910-017-0232-7
|View full text |Cite
|
Sign up to set email alerts
|

Participatory improvement of a template for informed consent documents in biobank research - study results and methodological reflections

Abstract: BackgroundFor valid informed consent, it is crucial that patients or research participants fully understand all that their consent entails. Testing and revising informed consent documents with the assistance of their addressees can improve their understandability. In this study we aimed at further developing a method for testing and improving informed consent documents with regard to readability and test-readers’ understanding and reactions.MethodsWe tested, revised, and retested template informed consent docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The data that support the findings of this study Bossert et al, 31 Dry et al, 69 Filocamo et al, 40 Forrest et al, 34 Kimball et al, 16 McCarty et al, 12 Mitchell et al, 3 Molster McWhirter et al, 50 Jenner et al, 53 Lemke et al, 61 Watson Chalmers et al, 4 Coors et al, 32 Godard et al, 47 Kimball et al, 16 Mitchell et al, 3 O'Doherty et al, 57 Olaitan et al, 67 Olson et al, 36 Rotimi et al, 62 Terry et al, 37 Terry et al, 43 Wilcox et al, 21 Lemke et al, 61 McCarty et al, 12 Mitchell et al, 3 Jenner et al, 52 Lemke et al, 60 Boyer et al, 60 Filocamo et al, 40 Levitt and Weldon, 70 Mitchell et al, 3 Terry et al, 43 Wilcox et al, 21 Rabeharisoa McCarty et al, 12 Mitchell et al, 3 Olson et al, 36 Wilcox et al, 21 McWhirter et al, 50 Lemke Godard et al, 47 Kimball et al, 16 Lemke et al, 33 Levitt, 56 Marsh et al, 62 Mitchell et al, 3 Rotimi et al, 61 Terry et al, 37 Wilcox et al, …”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tsupporting
confidence: 92%
See 1 more Smart Citation
“…The data that support the findings of this study Bossert et al, 31 Dry et al, 69 Filocamo et al, 40 Forrest et al, 34 Kimball et al, 16 McCarty et al, 12 Mitchell et al, 3 Molster McWhirter et al, 50 Jenner et al, 53 Lemke et al, 61 Watson Chalmers et al, 4 Coors et al, 32 Godard et al, 47 Kimball et al, 16 Mitchell et al, 3 O'Doherty et al, 57 Olaitan et al, 67 Olson et al, 36 Rotimi et al, 62 Terry et al, 37 Terry et al, 43 Wilcox et al, 21 Lemke et al, 61 McCarty et al, 12 Mitchell et al, 3 Jenner et al, 52 Lemke et al, 60 Boyer et al, 60 Filocamo et al, 40 Levitt and Weldon, 70 Mitchell et al, 3 Terry et al, 43 Wilcox et al, 21 Rabeharisoa McCarty et al, 12 Mitchell et al, 3 Olson et al, 36 Wilcox et al, 21 McWhirter et al, 50 Lemke Godard et al, 47 Kimball et al, 16 Lemke et al, 33 Levitt, 56 Marsh et al, 62 Mitchell et al, 3 Rotimi et al, 61 Terry et al, 37 Wilcox et al, …”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tsupporting
confidence: 92%
“…Also, three papers did not refer to a specific biobank, and the public involved gave input on hypothetical studies that would become actual biobanks in the future. [31][32][33] More details (including the method of involvement, the tasks addressed by involvement and a short description of the public involved) of the biobanks covered in the studies included can be found in Table 1. Additionally, a Supplementary Table in Appendix 3 provides details on each biobank.…”
Section: Name Of the Biobank (When Available) Countrymentioning
confidence: 99%
“…The postal survey was part of a larger project aimed at user-testing and revising an informed consent form for biobank research ( Bossert et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Study designers should take care to incorporate proper language into the informed consents of participants to allow for the request of additional blood draws or sample collections and for the future use of their clinical samples for the purposes of standards and assay development. [14][15][16] Such studies should also ensure that well-established chain-of-custody, sample handling, and sample storage procedures are in place to maintain the quality of these valuable specimens. 17,18 A significant drawback of this approach is that often the samples may not have adequate characterization, may be of limited volume, and are proprietary to the study sponsors.…”
Section: Biological Reference Materials and International Standardsmentioning
confidence: 99%